Non-descent vaginal hysterectomy in women with previous caesarean section scar: our experience - Maiti, G. D.; Pillai, Ashok; Jose, Tony; Lele, P. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is one of the common gynaecological major surgeries performed worldwide. In spite of technological advancement with laparoscopic and robotic hysterectomy conventional hysterectomy through vaginal route of nonprolapse uterus popularly known as, Non-Descent Vaginal Hysterectomy (NDVH) remains a justifiable cost effective, cosmetically appealing option especially in resource-crunched developing country. NDVH in post caesarean scarred uterus too a technically challenged procedure requiring skills and expertise. Assessment of technical feasibility and safety of non-descent vaginal hysterectomy in women with previous caesarean section scar were studied. Methods: The study was a prospective observational study of 72 patients with LSCS scar requiring hysterectomy for benign conditions were selected based on the inclusion and exclusion criteria carried out from June 2012 to May 2017. Operating time, blood loss, surgical techniques, intra/postoperative challenges, conversion to laparotomy or laparoscopic assistance and length of hospital stay were recorded for each case. Patients were followed up till 03 months of surgery. Results: Vaginal hysterectomy was successful in all cases. Morcellation, bisection or myomectomy, were done in 86% cases. Two patients had bladder injury, which was repaired vaginally, two cases required support of laparoscopy. No patients needed blood transfusion. None of the patients were converted to laparotomy. Conclusions: Vaginal hysterectomy is a safe and effective procedure for benign non-prolapsed uteri in women with previous caesarean section scar when uterine size is less than 14 weeks. Standby operating laparoscopy provides added advantages to surgeon in doubtful or difficult cases to avoid conversion laparotomy.